Nutrition in hemodialysis patients previously on a supplemented very low protein diet - Vendrely, Benoît; Chauveau, Philippe; Barthe, Nicole; El Haggan, Wael; Castaing, Françoise; De Précigout, Valérie; Combe, Christian; Aparicio, Michel (Kidney international, 2003)
Nutrition in hemodialysis patients previously on a supplemented very low protein diet. Nutritional safety of protein-restricted diets in patients with chronic renal failure is controversial. In the present study, we have assessed the evolution of nutritional status after initiation of hemodialysis in patients previously treated by a supplemented very low protein diet (SVLPD). Nutritional data were prospectively collected during the first year of hemodialysis from 15 consecutive patients treated with a SVLPD (0.3 g protein/kg/day supplemented with essential amino acids, calcium, iron, and vitamins) and compared to 15 age- and gender-matched end-stage renal disease (ESRD) patients previously on a less-restricted diet (0.90 ± 0.21 g protein/kg/day) who started hemodialysis during the same period. Dual-energy x-ray absorptiometry (DEXA) was used to assess body composition at 0, 6, and 12 months. Hemodialysis prescriptions, biologic data and 3-day food records were collected every 3 months. Protein intake was higher than 1.2 g/kg/day in both groups as soon as 3 months after the start of hemodialysis. Albumin and prealbumin increased significantly during the first 6 months in all patients. Body mass index (BMI) increased in all patients (+0.97 ± 1.31 kg/m2; P < 0.001) reflecting a gain in fat mass in the overall population (+2.36 ± 2.94 kg/m2; P < 0.001) while lean body mass remained stable overall. Once on hemodialysis, SVLPD patients rapidly increased protein intake. Nutritional status improved in all patients, with a gain in fat mass in all, and a gain in lean body mass in SVLPD men only. These data indicate that treatment with a SVLPD prior to hemodialysis initiation is nutritionally safe.